2020
DOI: 10.1016/j.biocon.2020.108421
|View full text |Cite
|
Sign up to set email alerts
|

Choice of baseline affects historical population trends in hunted mammals of North America

Abstract: Establishing historical baselines of species' populations is important for contextualising present-day population trends, identifying significant anthropogenic threats, and preventing a cultural phenomenon known as 'shifting baseline syndrome'. However, our knowledge of historical baselines is limited by a lack of direct observation data on species abundance pre-1970. We present historical data of species-specific fur harvests from the Canadian government and Hudson's Bay Company as a proxy for estimating spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…, when the model projections start after the stock has been subject to unknown previous catches) are imprecise 96 . Recently, Collins et al 101 demonstrated that for eight species of Canadian mammals the use of 1850 rather 1970 as the baseline year resulted in a shift of four species from an increase to a decrease in population since 1970. For the SRW, in 2001, the IWC performed a global assessment to obtain an estimate of the initial population size 19 setting the pre-exploitation baseline in 1770.…”
Section: Discussionmentioning
confidence: 99%
“…, when the model projections start after the stock has been subject to unknown previous catches) are imprecise 96 . Recently, Collins et al 101 demonstrated that for eight species of Canadian mammals the use of 1850 rather 1970 as the baseline year resulted in a shift of four species from an increase to a decrease in population since 1970. For the SRW, in 2001, the IWC performed a global assessment to obtain an estimate of the initial population size 19 setting the pre-exploitation baseline in 1770.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, for example, a significant amount of habitat destruction and overexploitation of some species had occurred prior to the 1970s and therefore the LPI baseline is set at a significantly depleted reference point 37 . The year chosen as a baseline can affect the interpretation of the state of biodiversity in a particular region 149 . Without taking this into consideration, it is possible to underestimate the gravity of the decline in biodiversity or overestimate a recovery within any given landscape.…”
Section: ) Communication and Interpretation Of The Lpimentioning
confidence: 99%
“…However, comparisons between regions should be interpreted with care because the baseline of 1970 set for this analysis sets relatively different starting points for the state of species abundance for each region. The baseline year chosen can be important for assessing long-term trends (Collins, Böhm et al 2020), particularly in regions where high human impact has been prevalent over centuries. In the case of North America and Western Europe, the baseline of 1970 hides historical declines in species abundance which occurred as land use was transformed after the Industrial Revolution (Ellis, Klein Goldewijk et al 2010); post-1970 trends may therefore show fewer declines as populations stabilise but at lower numbers.…”
Section: Global and Regional Trends In Utilised Populationsmentioning
confidence: 99%